2001 a Mars Odyssey. - Cass, S. (IEEE spectrum)
Discusses the mission of the Mars Odyssey spacecraft launched in April 2001. Brief mention is made of the Thermal Emission Imaging System (Themis), Gamma Ray Spectrometer, and the Mars Radiation Environment Experiment (Marie)